REFLEXÕES SOBRE A QUALIDADE DOS SERVIÇOS SOCIOASSISTENCIAIS NO CONTEXTO DA POLÍTICA PÚBLICA DA ASSISTÊNCIA SOCIAL NA MICRORREGIÃO DE IVAIPORÃ - ESTADO DO PARANÁ 2008 - Scherpinski, Selma Regina Marques (2008)
The conception of social work as a citizen’s right is recent considering its public policy status conquered since Federal Constitution of 1988. As a result of that, social work has its own field limited by Social Work National Policy -“PNAS/2004”, from which we point out the services of social basic protection. With these foundations, this study has as objective to analyze the quality of the service provided for the user population of the social work services devoted to child and to teenager from 7 to 17 years old, in the small municipalities of Ivaiporã micro-region, in Paraná State. We limited as universe the mentioned services and as subjects the coordinators of social work services, the user families and one representative member of Social Work State Council – “CEAS”. The methodologycal procedures used in the investigation were: the bibliography research, the documental study, the form, the semi-structured interview and the participating observation. The exposition of the results was organized in three chapters. The first, entitled “The Social Work in the Context of Brazilian Social Protection System”, recovers the trajectory of social work policy. The second chapter, nominated “The Configuration of Social Work Policy in Micro-Region of Ivaiporã-Paraná”, explains the context of the space where the services of social basic protection to child and teenagers from 7 to 17 years old become concrete. The third chapter, “The Quality of Social Work Services in the Micro-Region of Ivaiporã – Concepts and Reality”, treats the category quality and the specificity of the services. In this chapter, we organized the dada and the statements in four axes: users’ relation with the social work services, social workers, planning and assessment and the intersection actions. We finished the work with a reflection about the quality parameters, making possible an analysis of contribution of the services in relation to the emancipation of the assisted families.